Analysis of Audit Tenure, Opinion Shopping, Company Growth, and Debt to Equity Ratio Effect on Audit Going Concern Opinion - Benyamin Immanuel; Rina Aprilyanti (eCo-Fin, 2019)
This study aims to obtain empirical evidence on the influence of audit tenure, opinion shopping, company growth and debt to equity ratio towards acceptance of going concern audit opinion. The population in this study is the audited financial statements of infrastructure, utility and transportation services companies listed on the Jakarta stock exchange in 2013-2016. Determination of sample is done by using purposive sampling with amount of sample counted 30 company during period of 4 years observation so that total of sample is 120 datas. This research use SPSS version 23 with test of descriptive statistical analysis and logistic regression analysis. The result of this research shows that company growth has a significant effect on the acceptance of going concern audit opinion, audit tenure does not have a significant effect to the acceptance of going concern audit opinion, opinion shopping does not significantly effect the acceptance of going concern audit opinion and debt to equity ratio going concern audit opinion. Through the simultan significant test showed that the results of the 3 independent variables are not simultaneously influential to the acceptance of going concern audit opinion